2018
DOI: 10.1002/eat.22864
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessment of maladaptive eating in children and adolescents with overweight or obesity

Abstract: Eating-related factors appear to be most strongly associated with LOC severity, while environmental factors were most associated with overeating severity. Interventions targeting maladaptive eating in youth with overweight/obesity may benefit from helping youth incorporate palatable foods and satisfy cravings in a planned and controlled manner, and enhancing awareness of social-contextual effects on eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 48 publications
2
61
0
Order By: Relevance
“…Intriguingly, studies examining both within‐ and between‐person relationships sometimes find vastly different results across levels of analysis: different results are sometimes found when we compare youth to each other (between‐person) versus themselves across time (within‐person), providing incentive to guard against the ecological fallacy. Goldschmidt et al () provide an example. They examined the correlates of overeating and loss of control over eating in 40 adolescents aged 8–14 with overweight/obesity in a two‐week EMA.…”
Section: Review Of Ema Studies Of Child and Adolescent Mental And Behmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, studies examining both within‐ and between‐person relationships sometimes find vastly different results across levels of analysis: different results are sometimes found when we compare youth to each other (between‐person) versus themselves across time (within‐person), providing incentive to guard against the ecological fallacy. Goldschmidt et al () provide an example. They examined the correlates of overeating and loss of control over eating in 40 adolescents aged 8–14 with overweight/obesity in a two‐week EMA.…”
Section: Review Of Ema Studies Of Child and Adolescent Mental And Behmentioning
confidence: 99%
“…They examined the correlates of overeating and loss of control over eating in 40 adolescents aged 8–14 with overweight/obesity in a two‐week EMA. Goldschmidt et al () found that when adolescents were compared to themselves across time (within‐person), they perceived greater loss of control over eating on occasions with more palatable compared to themselves on occasions with less palatable food. However, when adolescents were compared to each other (between‐person), adolescents who tended to perceive food as less palatable showed higher loss of control over eating, on average, showing an opposite relationship to that observed at the within‐person level.…”
Section: Review Of Ema Studies Of Child and Adolescent Mental And Behmentioning
confidence: 99%
“…Although there is consistent support for the role of state and trait NA in adults (Haedt‐Matt & Keel, ; Smith et al, ), some naturalistic pediatric studies utilizing ecological momentary assessment have not found a direct relationship between state NA and LOC‐eating (Goldschmidt et al, ; Hilbert, Rief, Tuschen‐Caffier, de Zwaan, & Czaja, ; Ranzenhofer et al, ). Inconsistencies observed in the pediatric literature may be due to key differences in emotion regulation across the developmental spectrum (Swanson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, for children of parents with higher self-efficacy, overeating and loss of control eating were more similar across high and low levels of emotional eating. Given that emotion-related factors have not been as consistently linked to the momentary occurrence of disordered eating behaviors in youth compared to adults (Goldschmidt et al, 2018;Hilbert, Rief, Tuschen-Caffier, de Zwaan, & Czaja, 2009;Ranzenhofer et al, 2014), it may be that parent-related factors partly account for this inconsistency. (Burton, Smit, & Lightowler, 2007;Hill, Weaver, & Blundell, 1991), though this relationship may be more nuanced in youth.…”
Section: Discussionmentioning
confidence: 99%